SCREENING OF ISOLATED FRACTIONS OF DENDROPHTHOE FALCATA METHANOL STEM EXTRACT FOR ITS EFFECTS ON REPRODUCTIVE FUNCTIONS OF MALE RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
In our previous study methanol crude extract of Dendrophthoe falcata Ettingsh (family-Loranthaceae), stem showed contraceptive like activities in male albino rats. In the present study proven fertile male rats were treated with different isolated fractions (Chloroform: Methanol) of D. falcata stem at 50 mg/rat/day for 60 days. On day 61th the animals were autopsied, testes and accessory sex organs i.e. epididymides, seminal vesicle, ventral prostate were dissected out and weighed. Sperm dynamics and serum testosterone level were assessed; also testicular histological studies were done. The sperm motility and density were significantly reduced in all the treatment groups. Testosterone levels were declined significantly. Evaluations of testicular cell dynamics and histological studies suggest disrupt or inhibited spermatogenesis.